PREPARATION, CHARACTERIZATION AND SAFETY ASSESSMENT OF COMBINATORIAL NANOPARTICLES OF CARVEDILOL AND SERICIN - SHARIQ, MOHAMMAD; ANSARI, TARIQUE MAHMOOD; KUSHWAHA, POONAM; PARVEEN, SABA; SHAMIM, ARSHIYA; AHSAN, FAROGH; TAHA KAZMI, MOHAMMAD (International Journal of Applied Pharmaceutics, 2022)
Objective: The objective of the study is to prepare and evaluate the safety assessment of novel combinatorial Nanoparticle formulation. Methods: Chitosan nanoparticles were prepared by the ionic gelation method with slight modification. Drug-drug interaction was evaluated by Fourier Transform Infra-Red Spectroscopy. Size, Polydispersity Index, Zeta potential, Transmission Electron Microscopy Characterizations were performed as per standard procedures. Acute and subacute toxicity assessments were done by the standard protocol of OECD guideline number 425 and 407, respectively. Results: Size and zeta-potential were found to be 186.7 nm and-12.0mV, respectively. TEM analysis showed uniform, smooth, and spherical-sized particles. FTIR analysis of carvedilol, sericin, and physical mixture showed no interaction between them. The safety evaluation of prepared nanoparticle which was found to be safe at a dose of up to 1000 mg/kg body weight in single-dose acute toxicity and multiple-dose subacute toxicity study. Biochemical estimations were statistically evaluated and no significant differences were found that the mean P-value is greater than 0.05 and Histopathological examination has shown no marked disparity when compared to the normal control group. Conclusion: It can be concluded that the prepared Nanoparticles are safe in rodents and can be preceded for further evaluation for its preclinical cardioprotective potential.